1951–2017 changes in the frequency of days with visibility higher than 10 km and 20 km in Italy. (1st October 2019) - Manara, Veronica; Brunetti, Michele; Gilardoni, Stefania; Landi, Tony Christian; Maugeri, Maurizio
Abstract: Daily visibility records of the Italian Air Force synoptic stations over the 1951–2017 period have been used to set up a monthly quality/homogeneity checked dataset of fraction of days with visibility higher than or equal to 10 km (fVV10) and 20 km (fVV20) at 12 UTC. This dataset has been used to calculate regional average fVV10 and fVV20 records for 5 Italian climatic regions. The fVV10 and fVV20 averages show a strong spatial variability with the lowest values in the Po plain, one of the most polluted areas of Europe. In agreement with the results reported in literature for Europe, fVV10 and fVV20 show a positive trend over the whole considered period due to a strong increase starting in the 1980s. Differently, in the previous period, visibility decreases. Moreover, moving from low level areas to mid and high level ones the trends become much weaker, highlighting how the signal decreases with elevation. The analyses performed removing the days with high relative humidity or considering only the clear-sky days show that relative humidity and cloudiness do not have any effect on the observed trends, suggesting that the main driving factor is aerosol load. This hypothesis is supported by the comparison of visibility records with modelled aerosol concentrations, atmospheric optical depth values and emission records. Finally, the trends of fVV10 and fVV20 are in very good agreement with Italian regional records of other variables linked to atmospheric turbidity, like sunshine duration and surface solar radiation. Highlights: New data set of Italian quality/homogeneity checked visibility records. 1951–2017 fraction of days with visibility higher than or equal to 10 km and 20 km. Visibility records show a positive trend over the whole considered period. Trends become weaker increasing the elevation. The main driving factor seems to be aerosol load.